Financial performance and reimbursement of pharmacist-led chronic care management. (30th September 2020) - Martin, Randy; Tram, Kathlynn; Le, Lan; Simmons, Crystal
Abstract: Purpose: The purpose of this study was to evaluate the financial performance and reimbursement of chronic care management (CCM) provided by clinical pharmacists in a primary care setting using Current Procedural Terminology codes that were added to the Medicare Physician Fee Schedule in 2017. Methods: A retrospective study assessing financial performance of pharmacist-led CCM was conducted for the 12-month period from May 1, 2018, through April 30, 2019, at an academic multiclinic medical practice. Pharmacist-led CCM encounters included a combination of telephone and in-clinic visits. Return on investment, a ratio of net income to financial investment, was the primary outcome. Secondary outcomes included the number of CCM encounters, time spent by pharmacists delivering CCM (ie, "time-on-task"), and third-party claim reimbursement. Result: Sixty-five patients were enrolled in CCM during the 12-month study period. Pharmacists provided 236 CCM encounters, including 31 enrollment visits and 102 hours of clinical time-on-task. Gross revenue for CCM during the 12-month period was $7, 433.91, and expenses totaled $6, 430.36, resulting in a 15.6% return on investment. Out of 158 CCM claims, 131 (83%) were paid and 27 (17%) were unpaid or remained in adjudication at study completion. Conclusion: Pharmacist-led CCM resulted in a modest positive return on investment compared to other reimbursable pharmacy services. Practitioners should evaluate opportunities to synergize CCM with other fee-for-service and quality-based reimbursement programs.